(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The new age of technology has made its mark on all dimensions of social life. The justice system did not escape this influence, currently facing the need to adapt its principles and standards of criminal justice as a result of using Artificial Intelligence in the criminal investigation phase as well as in other stages of the criminal process. “Sweetie” is by far one of the most disputed means of criminal investigation that puts both the theory and the criminal procedural practice to the test. Through this interdisciplinary study we propose an analysis regarding the new means of investigation, trying to identify the advantages and disadvantages of using new technologies in the criminal trial, with a detailed description of the instrument “Sweetie” and of some cases in which it was used.